2019
DOI: 10.5935/abc.20190114
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sirtuin 1, 3 and 6 Levels in Acute Myocardial Infarction Patients

Abstract: Background Sirtuins may act in many cellular processes like apoptosis, DNA repair and lipid/glucose metabolism. Experimental studies suggested some sirtuin types may have protective effects against endothelial dysfunction, atherosclerosis, cardiac hypertrophy and reperfusion injury. Data about sirtuins in acute myocardial infarction (AMI) patients are scarce. Objectives To investigate temporal changes of serum sirtuin 1,3 and 6 levels in AMI patients; to compare the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
9
2
Order By: Relevance
“…Our findings indicated that tobacco consumption reduces the proteins involved in cell survival including SIRT1, SIRT3, and Klotho, and increases the rate of apoptosis ( Figures 5 – 8 ). Many cell functions, such as proliferation, apoptosis, cell survival, and response to stress, are mediated by class III histone deacetylases enzymes through deacetylating target proteins ( Kiziltunc et al, 2019 ). A number of studies have reported that SIRT1, one of the members of class III histone deacetylases enzymes, inhibits apoptosis in cardiomyocytes ( Tanno et al, 2010 ; Yu et al, 2016 ) and its reduction is associated with various cardiovascular pathologies such as cardiac hypertrophy and the severity of heart failure ( Kong et al, 2010 ; Sosnowska et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that tobacco consumption reduces the proteins involved in cell survival including SIRT1, SIRT3, and Klotho, and increases the rate of apoptosis ( Figures 5 – 8 ). Many cell functions, such as proliferation, apoptosis, cell survival, and response to stress, are mediated by class III histone deacetylases enzymes through deacetylating target proteins ( Kiziltunc et al, 2019 ). A number of studies have reported that SIRT1, one of the members of class III histone deacetylases enzymes, inhibits apoptosis in cardiomyocytes ( Tanno et al, 2010 ; Yu et al, 2016 ) and its reduction is associated with various cardiovascular pathologies such as cardiac hypertrophy and the severity of heart failure ( Kong et al, 2010 ; Sosnowska et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum SIRT1 level was found to be significantly higher in patients with LVH compared to those without LVH and to healthy subjects; multivariate logistic regression analysis revealed that increased serum SIRT1 concentration independently predicted LVH in patients with hypertension. Another recent human study on SIRT1 concentration was reported by Kızıltunç et al 39 They assessed temporal changes of serum sirtuin1 in 40 patients with acute myocardial infarction (AMI) compared to subjects with normal coronary arteries and found no differences between AMI patients and the latter group. In our population of patients with end-stage kidney disease on maintenance hemodialysis no differences in sirtuin1 levels between patients with LVH or other known cardiovascular disease and without was found.…”
Section: Discussionmentioning
confidence: 99%
“…The sirtuins (SIRTs) are a family of nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylases. There are seven closely related SIRT family members (Sirt1-7), and these are divided into four classes (144)(145)(146)(147). The best-known function of SIRTs is deacetylation (148).…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%